(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Article is dedicated to outpatient management of adults and children with urolithiasis. We have developed standards of equipment and recomendations of outpatient clinics managing urolithiasis based on our own long-term clinical experience analysis and international publications. Suggested protocol corresponds to basic aspects of diagnostic and treatment of patients with utolithiasis in outpatient conditions. Diagnostic and therapy procedures are divided into obligate and additional, used in children, young patients and in complicated patients. It was shown how important to determine conservative management individually according to detected risk factors, metabolic changes, physicochemical nature of calculi, co-morbidity and underwent surgical invasions of urinary tract in anamnesis of adults and children. Indications for phytotherapy, balneal and physiotherapeutic procedures were established. The necessity of multidisciplinary principal of urolithiasis management is shown. Long-term researches provided in Scientific Research Institute of Urology proved the necessity of standardized complex approach in investigation, outpatient surveillance and management of patients with urolithiasis in conditions of succession between outpatient and inpatient clinics, mutually responsible for management results. This measures may lead to statistically significant decrease of stone formation recurrence in more than 2.5-fold.